PELAYANAN PROGRAM BERAS MISKIN DI KELURAHAN MALENI KECAMATAN BANAWA KABUPATEN DONGGALA - Zainal, Mohammad (Katalogis, 2016)
This research aims at describing the rice for poor services in Maleni, Banawa District, Donggala. The methode used is descriptive qualitative research method and data collection techniques are observations , interviews, and documentattions. The Informanst were selected by using puposive sampling technique and seven informants were selected. The results show that the services is not optimal, although aspect reliability, responsivenees, assurance, Empathy have been good, but from the aspect of Tangibles has not not been good.Â